2014
DOI: 10.1038/ncomms5696
|View full text |Cite
|
Sign up to set email alerts
|

TSC1 controls macrophage polarization to prevent inflammatory disease

Abstract: Macrophages acquire distinct phenotypes during tissue stress and inflammatory responses, but the mechanisms that regulate the macrophage polarization are poorly defined. Here we show that tuberous sclerosis complex 1 (TSC1) is a critical regulator of M1 and M2 phenotypes of macrophages. Mice with myeloid-specific deletion of TSC1 exhibit enhanced M1 response and spontaneously develop M1-related inflammatory disorders. However, TSC1-deficient mice are highly resistant to M2-polarized allergic asthma. Inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
240
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(260 citation statements)
references
References 61 publications
17
240
1
2
Order By: Relevance
“…These findings indicate that activated mTOR may limit pro-inflammatory responses. On the contrary, other studies indicated that TSC1-deficient macrophages produced elevated pro-inflammatory cytokines including TNF-a, IL12p40, and IL-6 in response to multiple TLR ligands 19,23 . Moreover, TSC1-deficient BMDMs treated by LPS secreted more of the pro-inflammatory cytokines such as IL-6 and TNF-a but less of the anti-inflammatory cytokine IL-10 24 .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…These findings indicate that activated mTOR may limit pro-inflammatory responses. On the contrary, other studies indicated that TSC1-deficient macrophages produced elevated pro-inflammatory cytokines including TNF-a, IL12p40, and IL-6 in response to multiple TLR ligands 19,23 . Moreover, TSC1-deficient BMDMs treated by LPS secreted more of the pro-inflammatory cytokines such as IL-6 and TNF-a but less of the anti-inflammatory cytokine IL-10 24 .…”
Section: Introductionmentioning
confidence: 85%
“…In addition, TSC1-deficient macrophages in response to LPS stimulation produce elevated pro-inflammatory cytokines, such as TNF-a, IL-12, and IL-6 19,23,24 . The reasons for this inconsistency are unclear, possibly due to the different cell types and duration of mTOR inhibition with Rapa or mTOR deletion used in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the expression of Foxp3 control immune responses by their suppressive activity [108]. GM-CSF, TLR ligands and IL-4 promote activation of mTORC1 (figure :10) and mTORC2 (figure :11) in the immune cells, more specifically DCs, neutrophils, monocytes and macrophages [109]- [120]. The activation of mTORC1 and mTORC2 controls a wide range of basic cellular processes such as protein translation and synthesis, cell growth, metabolism and anabolic processes.…”
Section: B Cytoscapementioning
confidence: 99%